Levantamento florístico da Praça Coronel Moura, Botucatu, SP - Roxo, Fábio Fernandes [UNESP] (2009)
Modern society is living a revolution concerning environment concepts. There is a necessity to preserve the forest and to find different sources of energy and renewable material. Environmental education is important to make the new generation conscious. Thus, environment education in public square garden is a very interesting alternative in big cities where the young generation have no contact with nature. The present work has the objective of making an inventory of the Coronel Moura square garden in Botucatu, helping professors to identify plant diversity in the square. We visited the square every month from March to November. The species were identified using botanic identification manuals and comparing them with Botucatu herbarium collection. We found 34 species from 24 different families. The specie more frequently found in the square was the popular known sibipiruna, and a lot of species were presented only with one individual. The species presented in the square are enough to make activities about environment education. The knowledge about the diversity of plants, can help scholars to develop educational projects at Coronel Moura square.